Suitability of potato variety Kufri Surya for early planting under warmer condition in the Sone riverbed of Patna district in Bihar - Singh, S K; Lal, S S (Potato Journal, 2016)
The area under autumn/early potato crop in Bihar is around 15%. The productivity of early potato crop is very low due to high temperature prevailing during growth and development period of the crop. Kufri Surya, a heat tolerant variety of potato developed by Central Potato Research Institute, Shimla, performs better than other varieties when temperatures are higher during planting and early growth period. The field trials were conducted in randomized block design during autum/ winter season of 2011-12 and 2012-13 at farmer’s fields in participatory mode with the objective to assess the suitability of potato variety Kufri Surya for early planting under warmer condition in the Sone riverbed of Patna district in Bihar. The potato variety Kufri Surya recorded higher emergence percentage, significantly taller plants, more number of leaves per plant, higher LAI as compared, to potato cultivar Lal Gulab. It also produced highest total tuber yield, aggregate tuber population, average tuber weight, nutrient uptake, gross return and net return with recommended package of practices. Kufri Surya also produced 26.4% and 5.7% higher total tuber yield and total tuber number, respectively as compared to potato variety Lal Gulab at farmer’s management level. It also recorded 50.5 and 63.2% higher marketable tuber yield at farmer’s management and improved package of practice, respectively.